2017
DOI: 10.3762/bjoc.13.190
|View full text |Cite
|
Sign up to set email alerts
|

High-speed vibration-milling-promoted synthesis of symmetrical frameworks containing two or three pyrrole units

Abstract: The pseudo-five-component reaction between β-dicarbonyl compounds (2 molecules), diamines and α-iodoketones (2 molecules), prepared in situ from aryl ketones, was performed efficiently under mechanochemical conditions involving high-speed vibration milling with a single zirconium oxide ball. This reaction afforded symmetrical frameworks containing two pyrrole or fused pyrrole units joined by a spacer, which are of interest in the exploration of chemical space for drug discovery purposes. The method was also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…We found that the target compounds 27 were readily accessible, although in diminished yields compared to their simpler analogues 17 , probably owing to the fact that the formation of 27 involves seven individual steps ( Scheme 18 ). 34 Similarly, symmetrical aromatic compounds containing two acetyl groups were also employed as starting materials for pseudo-five component reactions leading to systems containing two pyrrole units joined by a spacer (compounds 28 ) ( Scheme 19 ). 29 …”
Section: Mechanochemical Multicomponent Reactions For the Synthesis Omentioning
confidence: 99%
“…We found that the target compounds 27 were readily accessible, although in diminished yields compared to their simpler analogues 17 , probably owing to the fact that the formation of 27 involves seven individual steps ( Scheme 18 ). 34 Similarly, symmetrical aromatic compounds containing two acetyl groups were also employed as starting materials for pseudo-five component reactions leading to systems containing two pyrrole units joined by a spacer (compounds 28 ) ( Scheme 19 ). 29 …”
Section: Mechanochemical Multicomponent Reactions For the Synthesis Omentioning
confidence: 99%
“…This reaction can be regarded a chemo-differentiating ABB′ three-component process, where one of the components has two different roles in the reaction . Again having in mind the synthetic application of our transformation, the fact that compound 8 contains a β-enaminoester structural fragment encouraged us to demonstrate its applicability as a synthetic intermediate, and to this end we chose to study 8 as a substrate for our mechanochemical generalization of the Hantsch pyrrole synthesis. , As shown in Scheme , phenacyl iodide ( 9 ) was obtained by mechanochemical α-iodination of acetophenone with N -iodosuccinimide in the presence of TsOH, in a solvent-free reaction promoted by ball milling (20 Hz, 1 h) . To this reaction mixture were added compound 8 , CAN as a catalyst and silver nitrate to capture the HI released in the alkylation of 8 by 9 , and ball milling was continued under the same conditions for an additional hour to furnish the highly functionalized pyrrole derivative 10 in moderate yield.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Leonardi et al achieved a generalization of their previously published pyrrole synthetic protocol by the reaction between primary amines, β-dicarbonyl compounds and ketones with the support of high-speed vibration milling (HSVM). [68] They developed the pseudo-five-component, solvent-free reactions affording the formation of bispyrrolic systems from the substrates βdicarbonyl compounds, diamine derivatives and aryl ketones (Scheme 15). Here, the strategy of joining two or three pyrrole or fused pyrrole units by a spacer to form symmetrical compounds of interest was employed.…”
Section: Mechanochemical Solvent-free Synthesismentioning
confidence: 99%